Analisis Sistem Aplikasi Keuangan Tingkat Instansi Dengan Menggunakan Technology Acceptance Model Pada Kementerian Agama Kota Sibolga - Sultan Anggi (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
The SAKTI (Agency-Level Financial Application System) application is an information system developed by the Ministry of Finance of the Republic of Indonesia to manage financial processes in government agencies. This application is designed to support budget management and financial reporting more efficiently, accurately, and integratedly. The purpose of this study was to determine the extent to which the Agency-Level Financial Application System implemented in the Ministry of Religious Affairs of Sibolga City can run effectively and efficiently, and to analyze user acceptance of this application based on the Technology Acceptance Model (TAM) model. This study uses a qualitative method, which involves collecting data through direct observation, in-depth interviews, and collecting documentation, especially financial reports. Interviews were conducted with the Head of the Ministry of Religious Affairs Office of Sibolga City to obtain information related to their experiences and views on the use of the SAKTI Application. The object of this study is the implementation of the Agency-Level Financial Application System with the Technology Acceptance Model approach at the Ministry of Religious Affairs of Sibolga City. The researcher acted as a research instrument, where data was collected through interviews, observations, and documentation of financial reports generated from the use of this application. The results of the study indicate that the SAKTI Application at the Ministry of Religious Affairs of Sibolga City has proven effective in improving financial management. This application accelerates the financial reporting process and reduces manual errors that often occur in previous financial management systems. The resulting time efficiency and the application's ability to provide real-time financial monitoring are the main advantages that support the effectiveness and efficiency of this application in financial management. Based on the results of the study, it can be concluded that the SAKTI Application provides a positive contribution in increasing the efficiency and effectiveness of financial management at the Ministry of Religion of Sibolga City. Acceptance of this application is influenced by factors of ease of use and usability of the application, which are analyzed through the perspective of the Technology Acceptance Model. Keywords: Financial Application System, Institution, Technology Acceptance Model